Evaluation of DIAGNOdent Values Before and After the Application of Opaque Fissure Sealant to Permanent Teeth - S.Jalal Pourhashemi; Mohammad javad Kharazifard; Zahra Baniameri; Aylar Hasanzadeh (Islamic Dental Association of Iran, 2013)
Background and Aim: The ability of DIAGNOdent (DD) for detection of occlusal caries under sealant and its reproducibility is a matter of question for dentists. The aim of this study was to evaluate DD values before and after the application of opaque fissure sealant (FS) and to determine the reproducibility of DD for detection of occlusal caries under sealant .   Materials and Methods: This study was carried out on 42 extracted sound human premolar and third molar teeth. Two examinersassessed the deepest occlusal pit of teeth with DD Pen (Kavo, Germany). This evaluation was repeated one week later to assess DD reproducibility. Assessment with DD was also performed after acid etching and FS application. The results were recorded and analyzed using linear regression test and SPSS software .   Results: The intra-examiner reproducibility of DD was 75.49% and 77.56% for the first and second observers, respectively. The mean DD value after etching and FS therapy increased by 28 and 6 units, respectively .   Conclusion: DD has high reproducibility making it suitable for the monitoring of occlusal caries. However, DD value is influenced by the opaque sealant and thus, it should not be used as the sole device for detection of caries under sealants .